Cloning, expression, purification, and characterization of LC-1 ScFv with GFP tag - 卢敏 龚兴国 于红 郦剑勇 (Journal of Zhejiang University. B. Science, 2005)
Total RNA was isolated from the hybridoma cell line （LC- 1 ）, which secretes anti-lung adenocarcinoma monoclonal antibody, and was transferred into cDNA. Based on the FRl （framework region l） and FR4 conserved regions of LC-1 gene, the variable regions of heavy chain （Vh） and light chain （Vl） were amplified, and the Vh and modified Vl were connected to single chain Fv （ScFv） by SOE-PCR （splice overlap extension PCR）. The modified ScFv was fused with green fluorescent protein （GFP） and introduced into E. coli JM109. The fusion protein induced by lPTG （Isopropylthiogalactoside） was about 57000 on a 10% SDS-PAGE gel （10% Sds Polyacrylamide Gel Electrophoresis）, and primarily manifested as inclusion bodies. The renatured protein purified by Ni-NTA Superflow resins showed ability to bind to antigen on SPC-A-l lung adenocarcinoma. In addition, the induced host cells fluoresced bright green under 395 nm wavelength, which indicated that the expected protein with dual activity was expressed in the prokaryotic system. The ScFv with GFP tag used in this research can be applied as a new reagent to detect immunological dye, and provide a feasible way to detect adenocarcinoma in a clinical setting.